Investigation of the in vivo interaction between beta-lactamase and its inhibitor protein - SARIYAR AKBULUT, BERNA; BULDUM, GİZEM (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2015)
The affinity of beta-lactamase inhibitory protein (BLIP) for TEM-1 beta-lactamase has raised hopes in the challenge of protein-based inhibitor discovery for beta-lactamase-mediated antibiotic resistance. Currently, the effect of the formation of the beta-lactamase:BLIP complex in vivo in beta-lactam resistant bacteria is an open question. The scarcity of information to the extent to which BLIP can impair beta-lactamase activity inside cells has urged us to assess the in vivo efficacy of BLIP as a potent beta-lactamase inhibitor. To this end, beta-lactamase and BLIP were coexpressed in Escherichia coli. Simultaneous expression of beta-lactamase and BLIP and the formation of the TEM-1 beta-lactamase: BLIP complex in the periplasmic space of E. coli were verified by electrophoretic and Western blot techniques. Growth profiles of the cells expressing both beta-lactamase and its protein inhibitor, complemented with beta-lactamase activity measurements, suggested that BLIP synthesis retarded cell growth and reduced beta-lactamase activity. Although co-expression of beta-lactamase and its protein inhibitor did not completely impair cell growth, the specificity of BLIP enabled it to bind beta-lactamase in the bacterial periplasm, regardless of the crowding components.
Keywords: beta-lactamase; antibiotic resistance; BLIP; ESCHERICHIA-COLI; PHAGE DISPLAY; BINDING; RESISTANCE; ANTIBIOTICS; CLAVULANATE; CENTA